(untitled) (Globalization and Business, 2023)
The teaching process of economic sciences must serve to train the competitive staff that will be successful in the field of economic theory and practical economics.Under the formation of market economy and economic transformation, the neo-liberal economic theory replaced the teaching of Marxist political economy in the university education space, for which a favorable environment for the occupation of the prevailing position in the country and the university was caused by many external and internal factors.But, in fact, we have still taken a stand that promotes uni- lateral development of economic thinking and excludes the pluralism of scientific thinking and the development of critical thinking. In the modern conditions, the use of “laissez faire” doctrine without the realization of state regulation is an ab- straction from reality”.Among the challenges of teaching the economic sciences in Georgian universities is the issue of the “Course of Economic History”. From the higher education programs of the economy, the course of “history of economics” has been taken out,which in turn negatively affects the qualifications of the graduates of the economic program and the quality of knowledge. The Scientific study of economic processes cannot be done without consensual knowledge of traditional traditions and cultural-historical existence and genetic-historical analysis.Also, in the era of globalization and information technology development, new challenges emerged in the challenges of teaching economic science. It is important to introduce interdisciplinary approaches and methods of teaching. In the context of the information period, it is important to modernize economic programs in the form of graduates, who will be able to engage in e-governance, which should provide citizens with the use of new technologies in their decision-making process. In addition, the development of this direction will facilitate acceleration of processes of electronic democracy and make governance processes transparent. It is desirable to modernize educational programs through such training courses as “reengineering business processes for e-governance”, “geographical information systems for territorial governance”, “e-governance solutions support systems” etc.